Management and Implications of Severe COVID-19 in Pregnancy in the United Kingdom: Data From the UK OBSTETRIC Surveillance System National Cohort. Issue 4 (21st December 2022) - Vousden, N.; Ramakrishnan, R.; Bunch, K.; Morris, E.; Simpson, N.; Gale, C.; O'Brien, P.; Quigley, M.; Brocklehurst, P.; Kurinczuk, J.J.; Knight, M.
Abstract : ( Acta Obstet Gynecol Scand . 2022;101:461–470. doi: 10.1111/aogs.14329) With the inauspicious rise to dominance of the Sars-CoV-2 Delta variant (B.1.617.2) in the United Kingdom in May 2021, the proportion of pregnant women experiencing severe disease proliferated significantly [35.8% during the Alpha variant duration vs. 45% in the Delta-dominant duration, adjusted odds ratio (aOR): 1.53]. A high proportion of pregnant women with COVID-19 deliver prematurely, are admitted to intensive care, and have neonates that also require intensive care. Most data thus far have come from single-center cohorts with small sample sizes, and present conflicting conclusions. There is an urgent need to investigate the risks and outcomes of severe COVID-19 illness in pregnant women to update guidelines for clinical management and prevention practices.